Field Tests on the Attenuation Characteristics of the Blast Air Waves in a Long Road Tunnel: A Case Study. (24th April 2019) - Fang, Yong; Zou, Yi-Lun; Zhou, Jian; Yao, Zhi-gang; Lei, Shuai; Yang, Wenbo
Abstract : After an explosion occurs in a tunnel, the blast waves take on diverse forms of attenuation in different regions when it propagates along the tunnel. However, the prediction of the overpressure decay laws proposed in previous studies has not taken into account the influence of the different regions in the tunnel. The present paper uses the example of the Micangshan highway tunnel in China and considers many factors that influence the propagation of the blast waves by dividing the tunnel into four zones. The paper modifies the decay equation proposed by Smith and applies it to the Micangshan highway tunnel in China. The decay equations are different in different zones. Field tests in this tunnel show that the modified equation is more suitable to describe the attenuation of the blast waves in the tunnel than the original equation.